Analisis Hukum terhadap Praktik Jasa Sewa Pacar di Indonesia dalam Perspektif KUHPerdata - nabilla rahmadhani (Jurnal Hukum Lex Generalis, 2026)
Girlfriend rental services are currently quite popular in Indonesia. In practice, this service is based on an agreement involving several parties and there are rights and obligations that need to be carried out by each party. This study analyzes the validity of the agreement according to the valid terms of the agreement regulated by Article 1320 of the Civil Code and the legal protection that exists in the practice of this service. The results of the study indicate that the agreement that occurs in this practice is invalid because it does not meet the requirements of a halal causa which has the effect of being null and void by law so that legal protection cannot be carried out. Therefore, it is necessary to increase legal understanding regarding the validity of the girlfriend rental service business.